Pandangan Institusi Keuangan Islam Terhadap Audit Syariah - Wardayati, Siti Maria (LP2M IAIN Samarinda, 2016)
Islamic banking in Indonesia, is growing rapidly since the issuance of policies on Islamic Banking. In order to minimize the risk of problems in the banking system, made efforts to control the use of patterns and mechanisms are getting better and is comprehensive. Audit Sharia in the Islamic financial services means the accumulation and evaluation of evidence to determine and report the level of concordance between the information and the criteria established for the purpose of Shariah compliance. Audit should be conducted by a competent and independenOleh therefore, auditors are representatives of the shareholders who want jobs (investment) them according to the laws of Islamic Shari'a.